Experimental Characterization and Theoretical Calculations of Responsive Polymeric Systems - Khouri, Salim (University of Waterloo, 2010)
Due to their controllable size, low cytotoxicity, and unique architecture, cyclodextrin based pseudopolyrotaxanes have been developed to encompass a broad range of diverse medical and chemical engineering applications. The study of complexation between α-cyclodextrin (alfa-CD) grafted PEG segments on the surface of PAMAM dendrimers was carried out to investigate the physical properties and driving force of this so called host guest interaction. At pH of 10, complexation between alfa-CD and PEGylated-PAMAM occurred once alfa-CD was titrated to the PAMAM solution. However, at pH of 2 no binding took place until a critical alfa-CD concentration (C*) of ~ 8.0 mM was exceeded. The size of the nanostructures increased with alfa-CD concentration ranging from 0.5 to 25 mM at pH value of 2. From zeta potential measurements it was found that the PEGylated-PAMAM possessed positive charges, attributed to the protonation of primary amine groups on PAMAM chains that impart electrostatic repulsive forces to the system. As observed from DLS and SLS study at increasing alfa-CD concentration and pH values, the morphology of the complex changed from a start shaped to a Gaussian like structure. The dynamics and dimensions (length, diameter, translation and diffusion coefficients) of rod-like cellulose micro crystallites (whisker) were also investigated using simulated parameter estimation technique. For rod with L/d ratio equal to 17 (ROD 17), experimental D and Θ values produced length and diameter values showing close resemblance to experimental results with a significant reduction in the percentage error approaching 0.22 and 0.27% after 1000 iterations, respectively. The proposed approach provides a suitable and simple method to determine the length and diameter of rod-like nanoparticles, such as nanocrystalline cellulose.
Keywords: Responsive; Polymers; Chemical Engineering